Preparation method for compounding HE-Fe3Se4 / Se heterojunction on Mxene as high-performance sodium ion battery anode material
By compounding high-entropy Prussian blue on Mxene and forming HE-Fe3Se4/Se heterojunction, the problems of low conductivity and volume expansion of sodium ion battery anode materials are solved, and high-performance sodium ion battery anode materials are realized, which significantly improves the Cycle life and rate performance.
Patent Information
- Application Number
- CN202411180753.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional sodium ion battery anode materials have poor cycle life and rate performance due to low conductivity and large volume expansion, which limits the development of sodium ion batteries.
High-entropy Prussian blue is compositely synthesized on Mxene, and HE-Fe3Se4/Se heterojunction is formed by high-temperature calcination, combining MXene's conductive network and the carbon-selenium bond of Prussian blue to form a high-performance sodium ion battery anode material.
It achieves high reversible capacity and excellent rate performance, improves material structural stability, enhances electronic conductivity, and relieves volume expansion, providing low-cost, high-performance sodium ion battery anode material.
Smart Images

Figure CN119263283A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery, and in particular to a method for preparing a high-performance sodium ion battery anode by composite HE-Fe3Se4 / Se heterojunction on Mxene. Background Art
[0002] With the rapid development of renewable energy storage and portable electronics, there is an increasing demand for cheap and pollution-free electrical energy storage technologies. Lithium-ion batteries are widely adopted due to their high energy density and excellent durability. However, the shortage of lithium salt resources (only 0.0065% in the earth's crust) and the rising mining / refining costs have hindered the further application of lithium-ion batteries worldwide. In this context, researchers have begun to focus on other alkali metal ions to replace lithium-ion batteries, such as sodium-ion batteries (SIBs), which show good prospects for grid-level energy applications due to the physicochemical similarities between Na and Li, the abundant reserves of sodium (the reserves of sodium in the earth's crust are 2.36wt.%) and the low cost7,8. Anode materials are one of the main technical bottlenecks restricting the development of high-performance SIBs. Since the radius of Na+ (0.113nm) is larger than that of Li+ (0.076nm), traditional commercial graphite exhibits poor Na storage performance. Therefore, we need to find suitable anode materials that can both improve the charge transfer kinetics and alleviate the severe volume changes during repeated cycles to promote the development of Na-ion battery systems to meet the Na-ion demand.
[0003] In the current research, conversion materials represent a promising class of anode materials that can provide higher theoretical capacity. Transition metal selenides have become a research hotspot due to their excellent electronic / ionic conductivity and excellent reversibility. Among transition metal selenides, Fe3Se4 is favored by researchers due to its suitable theoretical capacity, abundant iron resources, and low price, and is considered to be a potential suitable candidate for sodium ion batteries (SIBs). However, due to the inherent low conductivity of Fe3Se4 materials and the large volume expansion leading to electrode pulverization and particle agglomeration, Fe3Se4 has unsatisfactory long cycle life and rate performance, which hinders its practical application.
[0004] To address these challenges, different teams have tried several strategies to solve these thorny problems, including (1) micro / nanostructure engineering. Nanostructures are well adapted to large volume changes during cycling while exposing more active sites; (2) carbon composites (graphene, carbon nanotubes), MXene (Ti3C2) and other material composites can further improve the overall conductivity of the material while alleviating the volume effect; (3) ion doping can change the crystal structure and electronic structure of the material, thereby changing the conductivity, energy band width and adjusting the band gap; especially with the increasing attention paid to high entropy materials in the field of energy storage, especially in the field of electrode material design, high entropy doping or multi-element doping strategies have become increasingly important; (4) heterostructure construction will construct an internal electric field, effectively enhancing the reaction kinetics.
[0005] Here, inspired by the above, high entropy Prussian blue was synthesized on MXene by a simple co-precipitation method, and HE-Fe3Se4 / Se / MXene was obtained after further high-temperature calcination and selenization. As a negative electrode material for sodium ion batteries, this composite material has good long cycle performance and rate performance. HE-Fe3Se4 / Se / MXene electrode at 10Ag -1 After 1000 cycles at a high current density, it has a capacity of 337 mAh g -1 The high reversible capacity and extremely low capacity decay rate per cycle are only 0.0106%, and at 30A g -1 323mA hg -1 Excellent rate performance. This excellent electrochemical performance can be attributed to the unique synergy between the materials. 1) Multi-element doping (high entropy doping) can effectively reduce the expansion and contraction of the lattice and improve the structural stability of the material; 2) MXene can provide a stable conductive network, improve the electronic conductivity of the material, and play a supporting role in alleviating volume expansion. At the same time, MXene also has a certain capacity contribution; 3) The C inside the Prussian blue is bonded to the selenium by carbon-selenium bonds to form a HE-Fe3Se4 and Se heterojunction, which improves the internal electric field of Fe3Se4 and effectively enhances the reaction kinetics; 3) The nano-size design gives the particles a larger surface area and provides more active sites. This work provides important clues for the selection and design of low-cost, high-performance anode materials for sodium-ion batteries. Summary of the invention
[0006] The main purpose of the present invention is to provide a method for preparing a high-performance sodium ion battery anode material by composite HE-Fe3Se4 / Se heterojunction on Mxene, and the produced anode material can greatly improve the performance of the sodium ion battery.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing a high-performance sodium ion battery anode material by composite HE-Fe3Se4 / Se heterojunction on Mxene, which specifically comprises the following steps:
[0008] Step 1: Synthesize high entropy Prussian blue composite MXene material, specifically including the following steps:
[0009] Step 11, mixing a certain amount of sodium ferrocyanide and a certain amount of etched and peeled MXene powder;
[0010] Step 12, adding a certain amount of deionized water to the mixture obtained in step 11, and ultrasonically treating it in an ice water bath for a period of time;
[0011] Step 13, mixing the mixed solution obtained in step 2 with a certain amount of NaCl;
[0012] Step 14: Add a certain amount of deionized water to the mixed solution of step 3 to fully dissolve it to obtain solution A;
[0013] Step 15, respectively taking a certain amount of cobalt sulfate heptahydrate, nickel sulfate hexahydrate, ferrous sulfate tetrahydrate, manganese sulfate tetrahydrate, and copper sulfate pentahydrate and mixing them;
[0014] Step 16, adding deionized water to the mixture in step 5 to obtain solution B;
[0015] Step 17, pouring solution A into solution B at a certain speed, and then adding a certain amount of deionized water;
[0016] Step 18, stirring magnetically for a period of time at room temperature;
[0017] Step 19, aging the mixed solution obtained in step 18 at room temperature for a period of time and then discarding the supernatant;
[0018] Step 110, centrifuging the mixed solution obtained in step 19;
[0019] Step 111, adding 30 ml of deionized water to the solution obtained in step 110 and washing by centrifugation for 3 times;
[0020] Step 112, drying the obtained HE-PBA / MXene precipitate in an oven for a period of time to obtain a HE-PBA / MXene material;
[0001] Step 2: Synthesize HE-Fe3Se4 / Se / MXene anode material, specifically including the following steps:
[0002] Step 21, mixing the HE-PBA / MXene prepared in step 1 with selenium powder and sulfur powder at a certain mass ratio of 1:3;
[0003] Step 22, in a N2 atmosphere, heating the mixture to a predetermined temperature at a certain heating rate, and calcining the mixture at the predetermined temperature for a period of time;
[0004] Step 23: After naturally cooling to room temperature, HE-Fe3Se4 / Se / MXene powder is obtained, which is the anode material.
[0005] The present invention also provides a method for preparing a coin-type button half-cell, which specifically comprises the following steps:
[0006] Step 31, mixing and dissolving the Fe3Se4 / Se / MXene anode material, Ketjen black and polyvinylidene fluoride obtained above in a certain weight ratio in N-methylpyrrolidone;
[0007] Step 32, grinding the product obtained in step 31, and casting the slurry obtained by grinding on a copper foil;
[0008] Step 33, placing the copper foil in a vacuum oven at a certain temperature to dry for a period of time;
[0009] Step 34, cutting the dried copper foil into electrode sheets of a certain size, wherein the electrode sheets have a certain amount of active material and the electrode sheets are anodes;
[0010] Step 35: In a glove box filled with argon, use the sodium sheet, glass fiber and NP005 as the cathode, separator and electrolyte respectively, and assemble the electrode sheet obtained in step 34 as the anode to obtain a half-cell.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] 1) By synthesizing high-entropy Prussian blue and introducing five transition metal cations, high-entropy doping can effectively reduce the expansion and contraction of the lattice and improve the structural stability of the material;
[0013] 2) Fe3Se4 nanoparticles formed by Prussian calcination as MOF have a larger surface area, providing more active sites;
[0014] 3) Introducing MXene with MXene template, MXene can not only provide a stable conductive network and improve the electronic conductivity of the material, but also serve as a matrix support, which can effectively prevent the structural collapse caused by the powdery material during charging and discharging, and at the same time has a certain capacity contribution;
[0015] 4) A simple and convenient method is used to synthesize sodium ion anode materials with high capacity and high stability, which is expected to achieve process scale-up. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a specific synthesis route of the anode material according to the present invention;
[0017] Figure 2 These are the XRD patterns of three anode materials: LE-FeSe / Se, HE-Fe3Se4 / Se, and HE-Fe3Se4 / Se / MXene;
[0018] Figure 3 This is the XPS full spectrum analysis curve of HE-Fe3Se4 / Se / MXene;
[0019] Figure 4 It is the SEM image of HE-Fe3Se4 / Se / MXene;
[0020] Figure 5 It is the CV curve of the half-cell using HE-Fe3Se4 / Se / MXene anode material;
[0021] Figure 6 It is the charge-discharge curve of the first three cycles of the charge-discharge test of HE-Fe3Se4 / Se / MXene at a current density of 0.1A / g;
[0022] Figure 7 This is a comparison chart of the rate performance of three anode materials: LE-FeSe / Se, HE-Fe3Se4 / Se and HE-Fe3Se4 / Se / MXene;
[0023] Figure 8 This is a long cycle comparison chart of three anode materials LE-FeSe / Se, HE-Fe3Se4 / Se and HE-Fe3Se4 / Se / MXene at a current density of 2A / g;
[0024] Fig. 9 This is a long cycle comparison chart of three anode materials LE-FeSe / Se, HE-Fe3Se4 / Se and HE-Fe3Se4 / Se / MXene at a current density of 10A / g;
[0025] Fig.10 It is a series of HE-HE-Fe synthesized at different temperatures x Se y / Se rate performance comparison chart;
[0026] Fig.11 It is a series of HE-HE-Fe synthesized at different temperatures x Sey / Se long cycle comparison at 2A / g current density;
[0027] Fig.12 It is a series of HE-HE-Fe synthesized at different temperatures x Se y Long cycle comparison of / Se at a current density of 10 A / g. DETAILED DESCRIPTION
[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0029] Example
[0030] A method for preparing a high-performance sodium ion battery anode material by composite HE-Fe3Se4 / Se heterojunction on Mxene, specifically comprising the following steps:
[0031] Step 1: Synthesize high entropy Prussian blue composite MXene (HE-PBA / MXene) material, specifically including the following steps:
[0032] Step 11, weigh 1.264 g (4 mmol) of sodium ferrocyanide (Na4Fe(CN)6 and 100 mg of etched and peeled MXene (Ti3C2) powder and place them in a 100 mL beaker;
[0033] Step 12, add 50 mL of deionized water to the beaker, and perform ultrasonic wave with the probe in an ice water bath for 2 hours;
[0034] Step 13, place the mixed solution obtained in step 2 and 15 g NaCl in a 500 mL beaker;
[0035] Step 14, add 150 ml of deionized water to the mixed solution of step 3 to fully dissolve, to obtain solution A;
[0036] Step 15, accurately weigh 140.5 mg (0.5 mmol) of cobalt sulfate heptahydrate (CoSO4·7H2O), 131.4 mg (0.5 mmol) of nickel sulfate hexahydrate (NiSO4·6H2O), 111.5 mg (0.5 mmol) of ferrous sulfate tetrahydrate (FeSO4·4H2O), 111.5 mg (0.5 mmol) of manganese sulfate tetrahydrate (MnSO4·4H2O), and 124.8 mg (0.5 mmol) of copper sulfate pentahydrate (CuSO4·5H2O) and place them in a 1000 ml beaker;
[0037] Step 16: Add 200 ml of deionized water to the beaker in step 5 to obtain solution B;
[0038] Step 17, add a magnetic stirring rotor to solution B and place the beaker on a magnetic stirrer for stirring;
[0039] Step 18, slowly pour solution A into solution B, and then add 500 ml of deionized water;
[0040] Step 19, magnetic stirring at room temperature for 2 h;
[0041] Step 110, aging the mixed solution obtained in step 19 at room temperature for 24 hours and then discarding the supernatant;
[0042] Step 111: centrifuge the mixed solution obtained in step 110 at 9000 rpm min -1 Centrifugal separation at a speed of 10000rpm;
[0043] Step 112, repeatedly adding 30 ml of deionized water to the precipitate separated in step 111 and centrifuging and washing the precipitate three times;
[0044] Step 113, drying the obtained HE-PBA / MXene precipitate in an oven at 60° C. for 12 h to obtain a HE-PBA / MXene material;
[0045] The ratio of each cation to Se in HE-Fe3Se4 / Se / MXene was obtained by ICP test, as shown in Table 1:
[0046] Table 1 ICP-MS test results
[0047]
[0048] Step 2: Synthesize HE-Fe3Se4 / Se / MXene anode material, specifically including the following steps:
[0049] Step 21, mixing the HE-PBA / MXene prepared in step 1 with selenium powder and sulfur powder in a mass ratio of 1:3 and placing them at both ends of the porcelain boat respectively;
[0050] Step 22, placing the porcelain boat in a tube furnace, and placing one end of the selenium powder close to the air inlet of the tube furnace;
[0051] Step 23, in a N2 atmosphere, heating to 700°C at a heating rate of 1°C / min, and calcining for 3 hours; during the calcination process, the selenium powder sublimates, and HE-PBA is a MOF, and the sublimated selenium powder can be adsorbed in the porous structure of HE-PBA;
[0052] Step 24: After naturally cooling to room temperature, HE-Fe3Se4 / Se / MXene powder is obtained, which is the anode material.
[0053] Step 3: Assemble the coin-type button half-cell, including the following steps:
[0054] Step 31, Fe3Se4 / Se / MXene anode material, Ketjen black (KB) and polyvinylidene fluoride (PVDF) are mixed and dissolved in N-methylpyrrolidone (NMP) in a weight ratio of 7:2:1;
[0055] Step 32, grinding the product obtained in step 31, and casting the uniform slurry obtained by grinding on a copper foil;
[0056] Step 33, placing the copper foil in a vacuum oven at 60° C. and drying for 8 h;
[0057] Step 34: Cut the dried copper foil into electrode sheets with a diameter of 12 cm. The mass loading of the active material in the electrode sheets is about 0.8 to 1.2 mg cm -2 , the electrode sheet is the anode;
[0058] Step 35. In a glove box filled with argon, use sodium sheet, glass fiber (GF / D) and NP005 (1.0M NaPF6 dissolved in diethylene glycol dimethyl ether solution) as cathode, separator and electrolyte, and the electrode sheet obtained in step 34 as anode for assembly to obtain a half-cell.
[0059] Comparative Example 1
[0060] The MXene powder in solution A in step 1 was removed to synthesize high entropy Prussian blue (HE-PBA).
[0061] Comparative Example 2
[0062] The five sulfates in step 15 of step 1 were replaced with 557.5 mg (2.5 mmol) of ferrous sulfate tetrahydrate (FeSO4·4H2O) to synthesize iron-based Prussian blue (LE-PBA).
[0063] Comparative Example 3
[0064] The high entropy Prussian blue (HE-PBA) obtained in Comparative Example 1 was prepared into an iron disulfide anode material by using the above step 2.
[0065] Comparative Example 4
[0066] The iron-based Prussian blue (LE-PBA) obtained in step 2 is prepared into an anode material by using step 2.
[0067] Comparative Example 5
[0068] In Comparative Example 3, the calcination temperature was changed to 500° C. for 3 h.
[0069] Comparative Example 6
[0070] In Comparative Example 3, the calcination temperature was changed to 600° C. for 3 h.
[0071] Comparative Example 7
[0072] In Comparative Example 3, the calcination temperature was changed to 800° C. for 3 h.
[0073] Figure 2 The phase compositions of three anode materials, LE-FeSe / Se, HE-Fe3Se4 / Se and HE-Fe3Se4 / Se / MXene, were verified by XRD powder diffraction technique; Figure 3 The HE-Fe3Se4 / Se / MXene anode material was analyzed by X-ray photoelectron spectroscopy, and the successful introduction of five elements, Co, Mn, Ni, Cu, and Ti in MXene, and the successful MXene composite were confirmed by XPS full spectrum analysis. Figure 4 The HE-Fe3Se4 / Se / MXene anode material was tested by scanning electron microscopy, and the MXene flakes can be clearly seen, proving the successful compounding of MXene; Figure 5 The CV curves of the first three cycles of HE-Fe3Se4 / Se / MXene at a scan rate of 0.1mV / s. The reduction peak at 1.71V is considered to be the characteristic peak of Se redox, and the remaining peaks are considered to be the characteristic peaks of Fe3Se4 reaction, which further proves the heterojunction structure of HE-Fe3Se4 / Se / MXene. Figure 5 The charge-discharge test platform corresponds to the CV peak position, and also shows the high specific capacity of HE-Fe3Se4 / Se / MXene material; Figure 7-Figure 9 The charge and discharge tests compared the rate performance of the three materials and the long cycle performance at current densities of 2A / g and 10A / g, highlighting the excellent electrochemical performance of HE-Fe3Se4 / Se / MXene materials; Figure 10-12 HE-HE-Fe was synthesized by selenization at different temperatures through charge and discharge tests x Se y / Se series materials to obtain the optimal selenization temperature.
[0074] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a high-performance sodium ion battery anode material by composite HE-Fe3Se4 / Se heterojunction on Mxene, comprising the following steps: Step 1: Synthesize high entropy Prussian blue composite MXene material, specifically including the following steps: Step 11, mixing a certain amount of sodium ferrocyanide and a certain amount of etched and peeled MXene powder; Step 12, adding a certain amount of deionized water to the mixture obtained in step 11, and ultrasonically treating it in an ice water bath for a period of time; Step 13, mixing the mixed solution obtained in step 2 with a certain amount of NaCl; Step 14: Add a certain amount of deionized water to the mixed solution of step 3 to fully dissolve it to obtain solution A; Step 15, respectively taking a certain amount of cobalt sulfate heptahydrate, nickel sulfate hexahydrate, ferrous sulfate tetrahydrate, manganese sulfate tetrahydrate, and copper sulfate pentahydrate and mixing them; Step 16, adding deionized water to the mixture in step 5 to obtain solution B; Step 17, pouring solution A into solution B at a certain speed, and then adding a certain amount of deionized water; Step 18, stirring magnetically for a period of time at room temperature; Step 19, aging the mixed solution obtained in step 18 at room temperature for a period of time and then discarding the supernatant; Step 110, centrifuging the mixed solution obtained in step 19; Step 111, adding 30 ml of deionized water to the solution obtained in step 110 and washing by centrifugation for 3 times; Step 112, drying the obtained HE-PBA / MXene precipitate in an oven for a period of time to obtain a HE-PBA / MXene material; Step 2: Synthesize HE-Fe3Se4 / Se / MXene anode material, specifically including the following steps: Step 21, mixing the HE-PBA / MXene prepared in step 1 with selenium powder and sulfur powder at a certain mass ratio of 1:3; Step 22, in a N2 atmosphere, heating the mixture to a predetermined temperature at a certain heating rate, and calcining the mixture at the predetermined temperature for a period of time; Step 23: After naturally cooling to room temperature, HE-Fe3Se4 / Se / MXene powder is obtained, which is the anode material.
2. A method for preparing a coin-shaped button half-cell, comprising the following steps: Step 31, mixing and dissolving the Fe3Se4 / Se / MXene anode material obtained in claim 1, Ketjen black and polyvinylidene fluoride in a certain weight ratio in N-methylpyrrolidone; Step 32, grinding the product obtained in step 31, and casting the slurry obtained by grinding on a copper foil; Step 33, placing the copper foil in a vacuum oven at a certain temperature to dry for a period of time; Step 34, cutting the dried copper foil into electrode sheets of a certain size, wherein the electrode sheets have a certain amount of active material and the electrode sheets are anodes; Step 35: In a glove box filled with argon, use the sodium sheet, glass fiber and NP005 as the cathode, separator and electrolyte respectively, and assemble the electrode sheet obtained in step 34 as the anode to obtain a half-cell.